Characterization of modified mesoporous silica nanoparticles as vectors for siRNA delivery - Anna Slita; Anna Egorova; Eudald Casals; Anton Kiselev; Jessica M. Rosenholm (Elsevier, 2018)
Gene therapy using siRNA molecules is nowadays considered as a promising approach. For successful therapy, development of a stable and reliable vector for siRNA is crucial. Non-viral and non-organic vectors like mesoporous silica nanoparticles (MSN) are associated with lack of most viral vector drawbacks, such as toxicity, immunogenicity, but also generally a low nucleic acid carrying capacity. To overcome this hurdle, we here modified the pore walls of MSNs with surface-hyperbranching polymerized poly(ethyleneimine) (hbPEI), which provides an abundance of amino-groups for loading of a larger amount of siRNA molecules via electrostatic adsorption. After loading, the particles were covered with a second layer of pre-polymerized PEI to provide better protection of siRNA inside the pores, more effective cellular uptake and endosomal escape. To test the transfection efficiency of PEI covered siRNA/MSNs, MDA-MB 231 breast cancer cells stably expressing GFP were used. We demonstrate that PEI-coated siRNA/MSN complexes provide more effective delivery of siRNAs compared to unmodified MSNs. Thus, it can be concluded that appropriately surface-modified MSNs can be considered as prospective vectors for therapeutic siRNA delivery. Keywords: Gene therapy, Nanocarriers, siRNA delivery, Mesoporous silica nanoparticles